2019
DOI: 10.1002/jimd.12151
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydrobiopterin treatment in phenylketonuria: A repurposing approach

Abstract: In phenylketonuria (PKU) patients, early diagnosis by neonatal screening and immediate institution of a phenylalanine‐restricted diet can prevent severe intellectual impairment. Nevertheless, outcome remains suboptimal in some patients asking for additional treatment strategies. Tetrahydrobiopterin (BH4) could be one of those treatment options, as it may not only increase residual phenylalanine hydroxylase activity in BH4‐responsive PKU patients, but possibly also directly improves neurocognitive functioning i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 93 publications
(191 reference statements)
0
5
0
1
Order By: Relevance
“…In 1999, Kure et al [ 10 ] found a reduced blood Phe concentration after the oral administration of BH4. BH4-responsive PAH deficiency is divided into complete responders and partial responders [ 11 ]. The complete responder means that the blood Phe concentration of patients can reach normal levels after BH4 medication, whereas the partial responder fails to reach the normal range.…”
Section: Introductionmentioning
confidence: 99%
“…In 1999, Kure et al [ 10 ] found a reduced blood Phe concentration after the oral administration of BH4. BH4-responsive PAH deficiency is divided into complete responders and partial responders [ 11 ]. The complete responder means that the blood Phe concentration of patients can reach normal levels after BH4 medication, whereas the partial responder fails to reach the normal range.…”
Section: Introductionmentioning
confidence: 99%
“…19 Indeed, it has been proposed that in addition to increasing residual PAH activity in BH 4 -responsive PKU patients, BH 4 may also improve neurocognitive functioning and thus also be given to BH 4 unresponsive PKU patients who do not show any effect on their hyperphenylalaninemia. 49 In addition to the enzyme stabilizing effect, there are several mechanisms underlying responsiveness to BH 4 for some PAH variants, such as the hyperbolic relationship between the activity and the concentration of the cofactor/ co-substrate BH 4 , as well as the protection of the enzyme from rapid oxidative inactivation. 50 Altogether, our results may indicate a similar multifactorial effect of BH 4 supplementation on TH and THD-associated mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical and pharmacological chaperones emerge as promising therapeutics that stabilize and reactivate the mutant enzyme, hence delaying or curing disease phenotypes [64,65]. For instance, the pharmacological chaperone sapropterin (Kuvan) has already been approved as the first nondietary treatment for patients suffering from phenylketonuria which results from a single amino acid alteration in phenylalanine hydroxylase (PHA) [66]. Furthermore, chemical chaperones have been demonstrated to enhance the activity of mutated PHA, mutated cystathionine beta-synthase known to be associated with homocystinuria, and mutated branched-chain alpha-ketoacid decarboxylase which is associated with maple syrup urine disease [67][68][69].…”
Section: Discussionmentioning
confidence: 99%